Analysis of Student Readiness in Facing Minimum Competency Assesment - Novrian Satria Perdana (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
In 2021 there will be a substitute for the National Examination, namely Minimum Competency Assessment and character surveys. The role of the AKM is used to measure literacy and numeracy competencies. To test the readiness of students and teachers, at the beginning of 2020 a rehearsal for the implementation of the AKM was held. Therefore, this study aims to analyze the perceptions of students' readiness in facing the Minimum Competency Assessment. This study applies a qualitative and quantitative approach by conducting surveys and interviews with students in public and private high schools and vocational high schools with high, medium, and low scores for the category of National Examination results in Aceh Province in 2019. The results of this study state that some Highest school and vocational high school students think that the AKM questions tested are not in accordance with the material in the learning process taught by teachers in schools so that they are not ready to face AKM if it is held this year.